(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Quaternary ammonium compounds (QACs) have represented one of the most visible and effective classes of antiseptics and disinfectant substances that are used in different parts of life including food production, water treatment, and healthcare such as hospitals to prevent infections and intoxications. The increased use of disinfectants containing QACs has raised concerns about the development of QAC resistance. Objective: To determine the frequency of antiseptic-resistant QACs (qacA/B qacC and qacE gene) among Staphylococcus aureus (S. aureus), recovered from topical wound infection. Methods: Two swab samples were collected from 200 patients complaining of burns, traumatic injury, and wounds after surgery, suspected isolates of S. aureus, which showed beta hemolysis on blood agar media further tested by inoculated on mannitol salt agar and incubated at 37°C for 24 hours, bacteria that showed the characteristic of the yellow colony were furthermore identified using VITEK-2 System. The efficacy of antiseptics Chlorhexidine (CLX), Benzalkonium (BZK), and Cetrimide was tested against S. aureus by well diffusion assay test and minimum inhibitory concentration procedure. The confirmed S. aureus isolates have been used for genomic DNA extraction from a fresh overnight culture after that DNA template was used to target (qacA/B, qacC and qacE gene) by using specific Primers sequences. Results: Of 71 S. aureus, a considerable number of isolates 68 (95.8%) were resistant to CLX. Moreover, a substantial number of isolates 67 (94.4%) resistant to Cetrimide. No sensitive rate to BZK was observed in all isolates. qacA/B gene was identified in 48 (67.6%), while qacC gene was detected in 66 (93.0%). Furthermore, qacE gene was detected in 69 (97.2%) of 71 S. aureus isolates. Conclusion: qacA/B, qacC and qacE genes that harbored resistance to QACs antiseptics are widespread among S. aureus isolates in wound and burn patients. Keywords: Quaternary ammonium compound, antiseptic resistance gene, Chlorhexidine (CLX), Benzalkonium (BZK), Cetrimide. Citation: Ahmed SS, Hassan JS, Mahdi QA. Detection of the quaternary ammonium compound antiseptic resistance gene (qacA/B, qacC and qacE genes) among Staphylococcus aureus recovered from wound infection. Iraqi JMS. 2025; 23(1): 103-112. doi: 10.22578/IJMS.23.1.12